Size-Controlled Ammonium-Based Homopolymers as Broad-Spectrum Antibacterials - Meltem Haktaniyan; Richa Sharma; Mark Bradley (MDPI AG, 2023)
Ammonium group containing polymers possess inherent antimicrobial properties, effectively eliminating or preventing infections caused by harmful microorganisms. Here, homopolymers based on monomers containing ammonium groups were synthesized via Reversible Addition Fragmentation Chain Transfer Polymerization (RAFT) and evaluated as potential antibacterial agents. The antimicrobial activity was evaluated against Gram-positive (M. luteus and B. subtilis) and Gram-negative bacteria (E. coli and S. typhimurium). Three polymers, poly(diallyl dimethyl ammonium chloride), poly([2-(methacryloyloxy)ethyl]trimethylammonium chloride), and poly(vinyl benzyl trimethylammonium chloride), were examined to explore the effect of molecular weight (10 kDa, 20 kDa, and 40 kDa) on their antimicrobial activity and toxicity to mammalian cells. The mechanisms of action of the polymers were investigated with dye-based assays, while Scanning Electron Microscopy (SEM) showed collapsed and fused bacterial morphologies due to the interactions between the polymers and components of the bacterial cell envelope, with some polymers proving to be bactericidal and others bacteriostatic, while being non-hemolytic. Among all the homopolymers, the most active, non-Gram-specific polymer was poly([2-(methacryloyloxy)ethyl]trimethylammonium chloride), with a molecular weight of 40 kDa, with minimum inhibitory concentrations between 16 and 64 µg/mL, showing a bactericidal mode of action mediated by disruption of the cytoplasmic membrane. This homopolymer could be useful in biomedical applications such as surface dressings and in areas such as eye infections.